Pelatihan Budidaya Ikan Lele di Desa Cikopomayak, Jasinga, Kab. Bogor, Jawa Barat - Tohirin, Tohirin (SYUKUR (Jurnal Inovasi Sosial dan Pengabdian Masyarakat), 2020)
In order to re-empower local economic potential, a breakthrough is needed in exploiting every advantage and opportunity to create business activities. In Cikopomayak Village, Jasinga District Bogor and Karang Asih Cikarang Residents through the Zoom Application or online, most of the people's livelihoods are farmers and small traders. The higher life needs have made the people of Cikopomayak Village and the people of Karang Asih Cikarang have to add more income. Cikopomayak Village and and Karang Asih Cikarang Residents have very good market potential, but not many people are able to fill this potential. One of the efforts that can be done is to cultivate catfish with a 120liter jumbo bucket plus kale cultivation. This business is deemed suitable for development by the community to maintain food security at home. For this reason, the importance of preparing food for families is very easy, especially during the current pandemic.